The Islamic Legal System in Malaysia and the Quest for Transformation in the 21st Century - Kamaruddin, Zaleha (INSI Publications, 2012)
This paper highlights some loopholes and proposes a plan of action to transform the current Islamic legal system in Malaysia. This transformation surpasses the well-publicized concept of harmonization between the Malaysian Sharia legal system and the civil law or the common practice of moulding and casting modern concepts into Islamic constructs. Seeing how the field of Islamic legal system has evolved over the last century from the resulting modernization, transformation is needed to meet the demands and challenges of the new century. This paper springs from an extensive research involving more than ten agencies related to the Islamic legal system in Malaysia. The challenges faced by these agencies, and the plausible solutions to jump-start the Islamic legal system’s transformational efforts are closely examined. The combined efforts of these ten agencies, represented by a joint taskforce, are vital to the success of any action plan to initiate the transformation of the Islamic legal system in Malaysia through the identification of any possible problems and suggesting their solutions. Transformation in this context involves resolving issues through the various processes of renewal (tajdid), reform (islah), revival (ihya’), change (taghyir), migration (hijrah), and evaluation (taqwim). All these approaches should be made through the concept of consultation (mushawarah) and research driven strategies. The current atmosphere in Malaysia is ripe for such an action, as the political leadership of the country has proposed a national transformation plan that covers all aspects of the society. Accordingly, the political will for such transformation is present, and this opportunity must not be wasted. The need for transformation has proven to be constructive in the enhancement of its intellectual dimensions and application to solve the problems faced by Muslims in this challenging millennium. It is hoped that the set of proposals put forward in this study will serve as a catalyst to rapidly transform the Islamic legal system of the country in particular, and in the process, improve its entire legal system in general.